Nervous System Infections and the Global Traveler - Reid, Savina; Thompson, Haley; Thakur, Kiran T. (Seminars in Neurology, 2018)
Neurological complications of infectious diseases are associated with high rates of morbidity and mortality. It is imperative that neurologists be up-to-date on current developments including typical and atypical presentations of neurological infections in travelers, diagnostic and treatment recommendations, and emerging pathogen resistance patterns to avoid fatal outcomes and long-term sequelae. This article will address concepts of emerging and reemerging infectious diseases, and will provide updates on the neurological manifestations of select emerging and reemerging infections, including Ebola virus, bacterial meningitis, enterovirus 71, Zika virus, cerebral malaria, and Japanese encephalitis. Emerging and reemerging neurotropic infectious diseases, including Zika virus, have recently been major global health threats. Factors contributing to the emergence of infectious diseases include closer contact with zoonoses, population growth in cities, globalization, environmental changes, and the rise in antibiotic resistance. Serotype replacement of bacterial meningitis, the possibility of viral persistence in the central nervous system in Ebola virus, antibiotic resistance of malaria, and the evolution of neurovirulent strains of Zika virus display some of the developing challenges that accompany various neurotropic infectious diseases. Neurologists should be aware of the factors contributing to the emergence and reemergence of neurotropic infectious diseases. As emerging and reemerging neurotropic infectious continue to be a major global health security threat, clinicians should be aware of the risks to travelers and current guidelines on prevention and management.
Keywords: emerging neurological infections; neurotropic infections in travelers; central nervous system infections; encephalitis; meningitis